URGENSI PENANAMAN NILAI-NILAI AGAMA TERHADAP KARAKTER ANAK - Cindy Dwita Putri S (Pusat Studi Gender dan Anak, 2021)
Every child has a different disposition from other children. The nature of the child is a characteristic of each individual. The nature of each child will grow and develop according to their social environment. This means the emergence of delinquency in children in various aspects is not only their fault but also one of the negative impacts of an uneducated environment. It is in this context that the family is the main pillar for the formation of children's personalities which needs to be done by instilling religious values in them from an early age. This of course is intended so that children have a personality that is not easily influenced by the negative impacts that occur in the wider scope of social life. This writing method uses a library research method using a qualitative research approach. The author in this case seeks to collect library data either through books, articles or previous studies. Then the writer analyzes the collection of concepts to obtain the essence of planting religious values on the character of the child.